2004
DOI: 10.1002/pola.20263
|View full text |Cite
|
Sign up to set email alerts
|

Metallo‐supramolecular block copolymer micelles: Improved preparation and characterization

Abstract: Micelles prepared from amphiphilic block copolymers in which a poly(styrene) segment is connected to a poly(ethylene oxide) block via a bis‐(2,2′:6′,2″‐terpyridine‐ruthenium) complex have been intensely studied. In most cases, the micelle populations were found to be strongly heterogeneous in size because of massive micelle/micelle aggregation. In the study reported in this article we tried to improve the homogeneity of the micelle population. The variant preparation procedure developed, which is described her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 21 publications
0
28
0
Order By: Relevance
“…[15] Dynamic light scattering [13] and cryo-TEM experiments [16] revealed a strong tendency of metallo-supramolecular micelles to aggregate in contrast to the analogous traditional diblock copolymer micelles, a phenomenon that can be suppressed by modifying the method of preparation of the micelle. [17] Unless metallo-supramolecular micelles were prepared in salt-screened solutions, their core size does not scale linearly with the degree of polymerization of core-forming blocks as expected from the classical theory for traditional micelles. [18] Metallo-supramolecular micelles are relatively stable in water and various organic solvents [13] due to the large binding constant of the terpyridine-ruthenimum complexes and high glass transition temperature for the core-forming block.…”
Section: Introductionmentioning
confidence: 99%
“…[15] Dynamic light scattering [13] and cryo-TEM experiments [16] revealed a strong tendency of metallo-supramolecular micelles to aggregate in contrast to the analogous traditional diblock copolymer micelles, a phenomenon that can be suppressed by modifying the method of preparation of the micelle. [17] Unless metallo-supramolecular micelles were prepared in salt-screened solutions, their core size does not scale linearly with the degree of polymerization of core-forming blocks as expected from the classical theory for traditional micelles. [18] Metallo-supramolecular micelles are relatively stable in water and various organic solvents [13] due to the large binding constant of the terpyridine-ruthenimum complexes and high glass transition temperature for the core-forming block.…”
Section: Introductionmentioning
confidence: 99%
“…The groups of Schubert, Gohy, and coworkers [39,43,90] have shown that, as for covalent analogues, amphiphilic AB metallo-block copolymers can self-assemble, to give various metal containing micellar architectures in solution. Their first report in this area detailed the self-assembly of a bis-terpyridine Ru(II) linked PS-b-PEO block copolymer (PS 20 -[Ru]-PEO 70 ) into spherical micelles, induced via the addition of a non-solvent for one of the blocks ( Figure 6).…”
Section: Metallo-supramolecular Block Copolymer Micellesmentioning
confidence: 98%
“…Thus, in theory, upon self-assembly into triblock micelles, cross-linking to give nanoparticles and subsequent selective PS core removal, the targeted core hollowed, hydrophobic nanocages incorporating a new PMA internal shell layer could be accessed. An asymmetric SCS Pd(II) pyridine complex linked triblock terpolymer was synthesized with the structure: poly(acrylic acid)-b-poly(methyl acrylate)-[Pd)-PS or PAA 90 -PMA 45 -[Pd)-PS 35 , upon polymerization with functional CRP initiator species. [48] This strategy relies upon the established complexation chemistries of the previous system, but utilizes reversible addition fragmentation chain transfer (RAFT) polymerization to synthesize a covalently linked amphiphilic diblock (PAA 90 -PMA 45 -[Pd) which, when complexed to a second block bearing a pyridine functionality, Figure 11.…”
Section: Metallo-supramolecular Block Copolymer Micellesmentioning
confidence: 99%
See 1 more Smart Citation
“…[68][69][70][71] Related end-functional polymers have been used for the stabilization of metallic nanoparticles either by polymer growth from initiators attached to the nanoparticle surface 72,73 or by the mixing of preformed end-functional polymers with nanoparticles. 60 Although such systems are of great potential use, the remainder of this highlight focuses on those systems in which metal species are complexed to highly functionalized polymer blocks.…”
Section: Preparation Of Ligand-functional Block Co-mentioning
confidence: 99%